2005
DOI: 10.1016/j.virol.2005.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a new Vesivirus from rabbits

Abstract: This report describes the isolation, cDNA cloning, complete genome nucleotide sequence, and partial characterization of a new cultivable calicivirus isolated from juvenile feeder European rabbits (Oryctolagus cuniculus) showing symptoms of diarrhea. Absence of neutralization by type-specific neutralizing antibodies for 40 caliciviruses and phylogenetic sequence comparisons of the open reading frame 1-encoded polyprotein with those of other caliciviruses demonstrate that this new calicivirus is a putative novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…This cultivable calicivirus was recently isolated from dead or diseased young rabbits with diarrhoea from a rabbitry in Oregon in the United States (Martín-Alonso et al 2005;Percy and Barthold 2007). Percy and Barthold (2007) commented that 'The importance of this isolate as a pathogen in commercial rabbitries is yet to be determined' (see also Martín-Alonso et al (2005) on this point).…”
Section: Rabbit Vesivirusmentioning
confidence: 99%
See 1 more Smart Citation
“…This cultivable calicivirus was recently isolated from dead or diseased young rabbits with diarrhoea from a rabbitry in Oregon in the United States (Martín-Alonso et al 2005;Percy and Barthold 2007). Percy and Barthold (2007) commented that 'The importance of this isolate as a pathogen in commercial rabbitries is yet to be determined' (see also Martín-Alonso et al (2005) on this point).…”
Section: Rabbit Vesivirusmentioning
confidence: 99%
“…Percy and Barthold (2007) commented that 'The importance of this isolate as a pathogen in commercial rabbitries is yet to be determined' (see also Martín-Alonso et al (2005) on this point). The virus's origin, host specificity, mode of transmission and possible utility as a BCA are also unclear, but warrant further investigation.…”
Section: Rabbit Vesivirusmentioning
confidence: 99%
“…Rabbit vesivirus (Martin-Alonso et al, 2005) was propagated using Vero cells cultured in minimum essential medium supplemented with foetal bovine serum (10%), and antibiotics.…”
Section: Cells and Virusesmentioning
confidence: 99%
“…4A). According to the previously published putative RaV processing map (Martin-Alonso et al, 2005), based on the substrate specificity found for calicivirus 3C-like protease (Wirblich et al, 1995), the estimated molecular masses for RaV non-structural and structural proteins would be 31.7 kDa (2AB), 39.1 kDa (putative NTPase 2C), 30.7 kDa (3A), 12.4 kDa (3B, genome linked protein VPg), 76.6 kDa (bifunctional protease-polymerase, 3CD) and 60.8 kDa (mature capsid protein, mCap). The Western blots using specific R␣2AB serum revealed the presence of a singlespecific reacting polypeptide of about 33 kDa (Fig.…”
Section: Structural Characterization Of Rav Rcsmentioning
confidence: 99%
See 1 more Smart Citation